KENDALA DAN SOLUSI PEMBELAJARAN DARING PADA MATA PEMBELAJARAN GEOGARFI DI SMA YAYASAN BUNDA PADANG - HASIYA ROHMAH; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The purpose of this study was to describe the constraints and solutions for online learning in geography subjects at the Bunda Padang Foundation Senior High School. This research was conducted in class XI Social Sciences SMA Yayasan Bunda Padang. This type of research is qualitative. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis used in this research is data collection, data reduction, data presentation and conclusions. The results showed that the obstacles experienced by students and teachers were poor internet networks, no internet quota for studying, students who were undisciplined and lazy when learning online and students did not understand the material provided by the teacher. The online geography learning solution provided by the teacher in the online geography subject is that the teacher is responsible for the obstacles experienced and then notifies the curriculum representative if there is a problem to provide advice. While the online learning solution for the geography subject that students do is looking for places with a good network and asking for hotspots/using wifi then in order to understand the material students ask for help from others to explain material they don't understand, watch YouTube, or study alone. by reading from the internet.